Online physical exercise program with music improves working memory - Tabei, Ken-ichi; Ogawa, Jun-ichi; Kamikawa, Chiaki; Abe, Makiko; Ota, Yoshinori; Satoh, Masayuki (Frontiers in Aging Neuroscience, 2023)
Objective: The spread of coronavirus disease (COVID-19) has limited the implementation of face-to-face non-pharmacological treatment for the prevention of dementia. As a result, online non-pharmacological treatment has become increasingly important. In this study, we used an online conferencing system to implement an online version of a physical exercise program with music, and examined its effect on cognitive function. Methods: The participants were 114 healthy older adults (63 men and 51 women; mean age of 70.7 years [standard deviation = 4.6]). Seventy-five participants were allocated to the physical exercise with music group (60 minutes, once a week, total 20 sessions), while the remaining 39 participants were assigned to the control group, and only underwent the examinations. In the physical exercise with music group, we performed neuropsychological examinations and brain tests both before and after the exercise program. Neuropsychological tests included the Mini-Mental State Examination, Raven’s Colored Progressive Matrices (RCPM), the Rivermead Behavioral Memory Test, graphic imitation, word fluency (WF) (animal names and initial sounds), and the Trail Making Test-A/B. As an assessment of brain function, we developed an online examination of subtle cognitive decline, including tests of number and word memory, spatial grasp, the N-back task, and change inference. Results: In the N-back task, the physical exercise with music group improved significantly relative to the control group (p = 0.008). Discussion: The present findings suggest that the online version of the physical exercise with music program improved working memory, which mainly involves the frontal lobe.